Good Governance di Era Digital: Studi Kasus Implementasi E-Government di Indonesia - Susniwati, Susniwati; Ardiyansah, Ardiyansah; Sukorina, Diana (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
This study aims to determine and analyze the implementation of Good Governance in the Digital Era: Case Study of E-Government Implementation in Indonesia, and to determine and analyze the Obstacles and Efforts to implement Good Governance in the Digital Era: Case Study of E-Government Implementation in Indonesia. This study is a qualitative descriptive study, namely a study that aims to describe and describe events or phenomena that occur in the field and present data systematically, factually and accurately regarding the facts or phenomena that occur in the field. The results of the study indicate that overall, the implementation of E-Government in Indonesia has had a positive impact on good governance or more transparent, accountable, and efficient governance. However, various challenges or obstacles such as the digital divide, data security, and infrastructure readiness, human resources still need to be overcome so that the goals of Good Governance in the digital era can be achieved optimally and provide real benefits to the community. To overcome obstacles in the implementation of Good Governance in the digital era requires a comprehensive strategy, starting from improving infrastructure, digital literacy, supporting regulations, to strengthening cybersecurity. With the right steps, digital transformation in government can run more effectively, improve the quality of public services, and realize a transparent and accountable government system